A Developer's Translation of Social Sustainability: Communities that "Take Care of Themselves". Issue 3 (3rd July 2021) - Suchowerska, Roksolana
ABSTRACT: Scholars consider socially sustainable communities to be equitable, diverse, connected and democratic. This article examines how a property developer translates and works with concepts of social sustainability, with implications for social cohesion and equity. It draws on interviews with managers and residents in two Australian neighbourhoods to illustrate how commercial translations of social sustainability can promote the agency of residents, albeit with the purpose of realising the developer's vision for the neighbourhood. The article highlights how property developers who focus on commercial goals face challenges in creating inclusive and deliberative forums through which residents keep the developer's priorities in check.